FROM THE SHORT ACTING NIFEDIPINE TO AMLODIPINE AND FIXED COMBINATIONS. HIGHLIGHTS THE PROBLEM FROM THE CURRENT GUIDELINES POINT OF VIEW - L. I. Katelnitskaya; L. A. Haisheva (Рациональная фармакотерапия в кардиологии)
Calcium antagonists (CA) therapy of patients with arterial hypertension is focused on the base of current recommendations. Results of some large clinical trials confirm high antihypertensive efficacy of this therapeutic class. Special attention is devoted to implementation of fixed combinations on the basis of CA. Advantages of these combinations in hypertension therapy are discussed.